Pengaruh Manajemen Shift terhadap Kinerja Karyawan dengan Burnout sebagai Variabel Moderasi pada UMKM Penyedia Makan Bergizi Gratis (MBG) - Balqis Zahwa Khoirunnisa; Rohimat Nurhasan (Jurnal EMT KITA, 2026)
This study analyzes the effect of Shift Work Time Management on Employee Performance and examines the moderating role of burnout among employees of Micro, Small, and Medium Enterprises (MSMEs) involved in the Free Nutritious Meals (MBG) program in Leles District, Garut Regency. A causal quantitative research design with a moderation approach was employed, involving a total sample of 60 respondents. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3 software. The findings indicate that Shift Work Time Management has a significant and positive effect on Employee Performance (path coefficient = 0.584; p-value = 0.000). Furthermore, burnout was found to negatively moderate this relationship (path coefficient = -0.312; p-value = 0.001), suggesting that higher levels of burnout weaken the positive influence of Shift Work Time Management on Employee Performance. These results support the Conservation of Resources Theory and emphasize that maintaining employees’ mental well-being is a crucial strategic factor for improving organizational performance, particularly in MSMEs that rely heavily on human labor.